2010
DOI: 10.5194/cp-6-155-2010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of orbital forcing on atmosphere and ocean heat transports in Holocene and Eemian climate simulations with a comprehensive Earth system model

Abstract: Abstract. Orbital forcing does not only exert direct insolation effects, but also alters climate indirectly through feedback mechanisms that modify atmosphere and ocean dynamics and meridional heat and moisture transfers. We investigate the regional effects of these changes by detailed analysis of atmosphere and ocean circulation and heat transports in a coupled atmosphere-ocean-sea ice-biosphere general circulation model (ECHAM5/JSBACH/MPI-OM). We perform long term quasi equilibrium simulations under pre-indu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…The evaluation of a 300-yr control simulation with ECHAM5/MPIOM already showed that the tropical sea surface temperature climatology is well simulated and that global-scale heat and freshwater-transport are in agreement with observations (Jungclaus et al, 2006). Furthermore, ECHAM5/MPIOM has been successfully applied to different paleoclimate states such as Mid-Holocene climate and transient Holocene climate simulations (Fischer and Jungclaus, 2010;Otto et al, 2009;Dallmeyer et al, 2010;Vamborg et al, 2011), Last Glacial Maximum simulations (Mikolajewicz, 2011;Arpe et al, 2011), Eemian climate simulations (Fischer and Jungclaus, 2010;Schurgers et al, 2006) and Eocene climate simulations (Heinemann et al, 2009).…”
Section: Ensemble Simulations With Echam/mpiommentioning
confidence: 85%
“…The evaluation of a 300-yr control simulation with ECHAM5/MPIOM already showed that the tropical sea surface temperature climatology is well simulated and that global-scale heat and freshwater-transport are in agreement with observations (Jungclaus et al, 2006). Furthermore, ECHAM5/MPIOM has been successfully applied to different paleoclimate states such as Mid-Holocene climate and transient Holocene climate simulations (Fischer and Jungclaus, 2010;Otto et al, 2009;Dallmeyer et al, 2010;Vamborg et al, 2011), Last Glacial Maximum simulations (Mikolajewicz, 2011;Arpe et al, 2011), Eemian climate simulations (Fischer and Jungclaus, 2010;Schurgers et al, 2006) and Eocene climate simulations (Heinemann et al, 2009).…”
Section: Ensemble Simulations With Echam/mpiommentioning
confidence: 85%
“…Transient simulations usually rely on earth system models of intermediate complexity , while general circulation models (GCMs) primarily are employed for equilibrium, snapshot simulations (Fischer and Jungclaus 2010;Govin et al 2012;Lunt et al 2013;Nikolova et al 2013;Otto-Bliesner et al 2013;Langebroek and Nisancioglu 2014). Recent model assessments find very low global annual mean warming during LIG, contrasting the proxy reconstruction estimate of 1-2 K warming (Masson-Delmotte et al 2013;Otto-Bliesner et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While these patterns agree qualitatively with proxy reconstructions, the models generally underestimate the magnitude of the changes Masson-Delmotte et al 2013;Lunt et al 2013;Otto-Bliesner et al 2013). Several models have the strongest warming occurring in the North Atlantic region as a consequence of retreating sea ice and changes in the ocean circulation (Fischer and Jungclaus 2010;Lunt et al 2013;Nikolova et al 2013;Otto-Bliesner et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, anomalously warm conditions in the Arctic stand in contrast to the global DJF cooling at 6, 9, 125, 405, and 416 ka. The Arctic warming is due to the remnant effect of the polar summer insolation through ocean-sea-ice feedbacks (Fischer and Jungclaus, 2010;Herold et al, 2012; Kleinen et al, 2014). Anomalous shortwave radiation during the Arctic summer leads to enhanced melting of sea ice and warming of the upper polar ocean.…”
Section: Djf Surface Temperature Anomaliesmentioning
confidence: 99%